INNV-02. RADIOGRAPHIC CHARACTERISTICS AND STEROID USAGE IN LASER INTERSTITIAL THERMAL THERAPY VERSUS MEDICAL MANAGEMENT FOR BIOPSY-PROVEN RADIATION NECROSIS AFTER STEREOTACTIC RADIOSURGERY OF BRAIN METASTASES. (9th November 2020) - Srinivasan, Ethan; Sankey, Eric; Grabowski, Matthew; Griffin, Andrew; Howell, Elizabeth; Otvos, Balint; Tsvankin, Vadim; Atik, Ahmet; Joshi, Krishna; Barnett, Gene; Fecci, Peter; Mohammadi, Alirezza
Abstract: INTRODUCTION: Radiation necrosis (RN) occurs in 9–14% of patients after stereotactic radiosurgery (SRS) for brain metastases (BM). Medical management (MM) with steroids is a common first-line therapy, with variable response and numerous side effects, especially regarding immunotherapy. Laser interstitial thermal therapy (LITT) has been introduced as an efficacious, steroid-reducing alternative, however limited data exists comparing LITT to MM. METHODS: Patients with biopsy-proven RN after SRS for BM who received LITT or MM at two academic centers were retrospectively reviewed. Treatment failure was defined as radiographic progression that necessitated a change in management. Measurements of total (TLV) and contrast-enhancing lesion volume (ceLV) were obtained from MRI by semi-automated analysis using the BrainLab iPlan Cranial 3.0 software. RESULTS: Eighty-one patients were followed for 11.7 (4.3–27.0) months and 57 (70%) received LITT. Steroid cessation occurred at a median of 37 days post-LITT compared to 162 days after MM (p< 0.01). Treatment failure occurred in 5% of LITT patients at 4.0 (3.2–4.8) months and 13% of MM patients at 4.4 (4.1–5.3) months (p >0.05). Patients were 3.2 times more likely to be weaned off steroids when treated with LITT compared to MM (p< 0.01), when controlled for age, pre-operative ceLV, and post-operative seizure on multivariate analysis. Both groups demonstrated decreasing TLV and ceLV between baseline and last follow-up MRI. At 6–9 months, the LITT cohort demonstrated a -59% change in ceLV compared to -7% with MM (p >0.05). The LITT cohort demonstrated a significant decrease in ceLV between scans at 0–2 and 6–9 months (p< 0.01). The MM group did not demonstrate a statistically significant decrease in ceLV until 12 months. CONCLUSION: This study suggests that LITT for RN significantly reduces the time to steroid cessation, and earlier radiographic response to treatment by LITT. Large, prospective trials are needed to validate these findings.